ETIKA PLATO DAN ARISTOTELES DAN RELEVANSINYA BAGI KONSEP KEBAHAGIAN DALAM ISLAM: Etika Plato dan Aristoteles dalam Perspektif Islam - Rusmini, Agustina (UIN Sunan Kalijaga Yogyakarta, 2023)
This research discusses the relevance of Plato and Aristotle's ethical views to the concept of happiness from the perspective of Islam. Ethics is a fundamental discipline in philosophy that examines morality and how humans live to achieve true goodness. In the history of traditional philosophy, ethics is divided into four branches: logic, metaphysics, epistemology, and ethics itself. Plato and Aristotle's ethical views regarding happiness emphasize the importance of moral virtues and self-improvement through the understanding of knowledge. Plato emphasizes the significance of philosophical thinking and the regulation of reason to attain a good and happy life. On the other hand, Aristotle sees moral goodness as the highest goal in human actions, where happiness is obtained through the development of good character and moral virtues. The perspective of Islam also emphasizes moral values and obedience to Allah as integral parts of achieving genuine happiness. Islamic ethics understands and considers previous philosophical thoughts, including the perspectives of Plato and Aristotle, to apply relevant ethical principles in the contemporary context. This research adopts the library research method, collecting data from various sources such as books, scholarly journals, and classical writings of Plato and Aristotle. The data analysis is descriptive and analytical, aiming to comprehend the classical ethical views and their relevance to the Islamic ethical perspective. The findings of this research indicate that there are similarities, differences, and relevance between the ethical views of Plato and Aristotle and the ethical perspective in Islam. The common ground is that the moral values advocated in both perspectives can be applied in the context of modern human life. Keyword: Etihcs, Plato, Aristotle, Perspective, Islam Abstrak Penelitian ini membahas tentang relevansi pandangan etika Plato dan Aristoteles terhadap konsep kebahagiaan dari perspektif Islam. Etika adalah disiplin pokok dalam filsafat yang mengkaji tentang moralitas dan bagaimana manusia hidup agar mencapai kebaikan yang hakiki. Dalam sejarah filsafat tradisional, etika terbagi menjadi empat cabang, yaitu logika, metafisika, epistemologi, dan etika itu sendiri. Pandangan etika Plato dan Aristoteles terkait kebahagiaan menekankan pentingnya kebajikan moral dan peningkatan diri melalui pemahaman pengetahuan. Plato menekankan pentingnya pikiran filosofis dan pengaturan akal untuk mencapai kehidupan yang baik dan bahagia. Sementara Aristoteles melihat kebaikan moral sebagai tujuan tertinggi dalam tindakan manusia, di mana kebahagiaan diperoleh melalui pembangunan karakter dan keutamaan moral yang baik. Perspektif Islam juga menekankan nilai-nilai moral dan ketaatan kepada Allah sebagai bagian dari mencapai kebahagiaan yang hakiki. Etika dalam Islam memahami dan mempertimbangkan pemikiran-pemikiran filosofis sebelumnya, termasuk pandangan Plato dan Aristoteles, untuk menerapkan prinsip-prinsip etika yang relevan dalam konteks zaman saat ini. Penelitian ini menggunakan metode library research atau penelitian kepustakaan dengan mengumpulkan data dari berbagai sumber, seperti buku, jurnal ilmiah, dan tulisan-tulisan klasik Plato dan Aristoteles. Analisis data bersifat deskriptif analitis untuk memahami pandangan etika klasik tersebut dan bagaimana pandangan-pandangan tersebut relevan dengan pandangan etika dalam Islam. Dari hasil penelitian ini, dapat ditemukan persamaan, perbedaan, dan relevansi dengan pandangan etika Islam adalah bahwa nilai-nilai moral yang diperjuangkan dalam kedua pandangan tersebut dapat diaplikasikan dalam konteks kehidupan manusia modern. Kata kunci: Etika, Plato, Aristoteles, Perspektif, Islam